The phytotherapic potential of the Chenopodium Ambrosioides L. in Dentistry (Research, Society and Development, 2020)
Objective: To perform a narrative bibliographic review addressing scientific research that demonstrates the phytotherapic potential of Chenopodium ambrosioides L. (mastruz) in dentistry. Methods: Scientific articles were selected from the databases: PubMED, BBO, LILACS, SCIELO, in addition to dissertations that met the requirements of the topic addressed, published in the period between 2010 and 2020. The research on the platforms took place through the following descriptors, in Portuguese and English: Chenopodium ambrosioides, mastruz, phytotherapy and dentistry. Results: After analyzing the data found, it was observed that Chenopodium ambrosioides L. is a plant native to Central and South America and is widely distributed throughout the Brazilian territory. Its use in folk medicine consists of the treatment of wounds, leukorrhea, inflammatory processes and as an anthelmintic agent. In dentistry, it acts as a potent anti-inflammatory, antifungal and antimicrobial, being able to interfere in the development of biofilm. Conclusion: The advances in studies with Chenopodium ambrosioides L. are quite significant. However, greater applicability of the plant in dentistry is essential through in vivo studies, providing a greater depth of these studies for more concrete analyzes.